Genetic Variability and Phylogenetic Relationships within Trypanosoma cruzi I Isolated in Colombia Based on Miniexon Gene Sequences - Claudia Herrera; Felipe Guhl; Alejandra Falla; Anabella Fajardo; Marleny Montilla; Gustavo Adolfo Vallejo; M. Dolores Bargues (Journal of Parasitology Research)
Phylogenetic studies of Trypanosoma cruzi have identified the existence of two groups: T. cruzi I and T. cruzi II. There are aspects that still remain unknown about the genetic variability within the T. cruzi I group. Given its epidemiological importance, it is necessary to have a better understanding of T. cruzi transmission cycles. Our purpose was to corroborate the existence of haplotypes within the T. cruzi I group and to describe the genetic variability and phylogenetic relationships, based on single nucleotide polymorphisms (SNPs) found in the miniexon gene intergenic region, for the isolates from different hosts and epidemiological transmission cycles in Colombian regions. 31 T. cruzi isolates were molecularly characterized. Phylogenetic relationships within T. cruzi I isolates showed four haplotype groups (Ia–Id), associated with their transmission cycle. In previous studies, we reported that haplotype Ia is mainly associated with the domestic cycle and domiciliated Rhodnius prolixus. Haplotype Ib is associated with the domestic cycle and peridomestic cycle, haplotype Ic is closely related with the peridomestic cycle, and haplotype Id is strongly associated with the sylvatic cycle. The phylogenetic methodologies applied in this study are tools that bolster the associations among isolates and thus shed light on Chagas disease epidemiology.